1998
DOI: 10.1177/011719689800700402
|View full text |Cite
|
Sign up to set email alerts
|

Invisible Visibility: Intergenerational Transfer of Identity and Social Position of Chinese Women in Belgium

Abstract: "The effects of migration on identity and the social position of Chinese women in Belgium were examined from an intergenerational perspective. At the macro level, policies and the general discourse on migration and migrants in Belgium were examined to assess the level of inclusion or exclusion of Chinese women.... The findings will show that although the Chinese are non-existent in official policy and statistics, they are set apart in mainstream society because of their different phenotypical traits. This lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…With this in mind, first, we detail the literature on focus groups and discuss the emergence of various focus group effects in our research. We next turn to the simultaneous household interview strategy and outline how this technique offers glimpses into assorted intergenerational perspectives (Jamal, 2006;Pang, 1998). We conclude with examples from our postinterview dialogues.…”
mentioning
confidence: 99%
“…With this in mind, first, we detail the literature on focus groups and discuss the emergence of various focus group effects in our research. We next turn to the simultaneous household interview strategy and outline how this technique offers glimpses into assorted intergenerational perspectives (Jamal, 2006;Pang, 1998). We conclude with examples from our postinterview dialogues.…”
mentioning
confidence: 99%
“…In this regard, because the Belgian Taiwanese immigrants are few in number and small in terms of their ethnic community scale, Pang applied the term "invisible" to describe the Taiwanese immigrant community's social status in Belgian mainstream society. Pang also indicated that the Belgian Taiwanese immigrant community has been ignored and under-represented in the mass media, immigrant policy debates, educational issues, the mainstream labor market, and academic research [23,26]. Thus, Lin proposed that it is urgently necessary to explore Belgian Taiwanese immigrants' lived experiences and other related topics in order to fill the existing research gap and improve the status of the "invisible" social and academic positions in which Taiwanese immigrants are situated [22].…”
Section: Taiwanese Immigrant Communities: Worldwide and In Belgiummentioning
confidence: 99%
“…During this period, the 1970s and early 1980s, I had the good fortune of teaching at the School of Oriental and African Studies, University of London, which gave me an opportunity to keep track of developments in the European Chinese community. By this time, the Man had expanded throughout Europe and dominated the Chinese restaurant trade in Britain, Holland, Belgium, and southern Germany-opening and operating over four hundred restaurants (see also Gutinger 1998;Pang 1998;Pieke and Benton 1998); they also moved into Canada during the 1980s (see Johnson 1994). Three extended families, in particular, became leading lights in the Toronto and the Vancouver communities.…”
Section: The Early Disapora Phasementioning
confidence: 99%